Comparison of the Anti-inflammatory Properties of Two Nicotinic Acetylcholine Receptor Ligands, Phosphocholine and pCF3-diEPP - Richter, Katrin; Papke, Roger L.; Stokes, Clare; Roy, Danika C.; Espinosa, Eduardo S.; Wolf, Philipp M. K.; Hecker, Andreas; Liese, Juliane; Singh, Vijay K.; Padberg, Winfried; Schlüter, Klaus-Dieter; Rohde, Marius; et al. (Frontiers in Cellular Neuroscience, 2022)
Activation of nicotinic acetylcholine receptors (nAChRs) expressed by innate immune cells can attenuate pro-inflammatory responses. Silent nAChR agonists, which down-modulate inflammation but have little or no ionotropic activity, are of outstanding clinical interest for the prevention and therapy of numerous inflammatory diseases. Here, we compare two silent nAChR agonists, phosphocholine, which is known to interact with nAChR subunits α7, α9 and α10, and pCF3-N,N-diethyl-N′-phenyl-piperazine (pCF3-diEPP), a previously identifiedd as an α7 nAChR silent agonist, regarding their anti-inflammatory properties and their effects on ionotropic nAChR functions. The lipopolysaccharide (LPS)-induced release of interleukin (IL)-6 by primary murine macrophages was inhibited by pCF3-diEPP, while phosphocholine was ineffective presumably because of instability. In human whole blood cultures pCF3-diEPP inhibited the LPS-induced secretion of IL-6, TNF-α and IL-1β. The ATP-mediated release of IL-1β by LPS-primed human peripheral blood mononuclear leukocytes, monocytic THP-1 -cells and THP-1-derived M1-like macrophages was reduced by both phosphocholine and femtomolar concentrations of pCF3-diEPP. These effects were sensitive to mecamylamine and to conopeptides RgIA4 and [V11L;V16D]ArIB, suggesting the involvement of nAChR subunits α7, α9 and/or α10. In two-electrode voltage-clamp measurements pCF3-diEPP functioned as a partial agonist and a strong desensitizer of classical human α9 and α9α10 nAChRs. Interestingly, pCF3-diEPP was more effective as an ionotropic agonist at these nAChRs than at α7 nAChRs. In conclusion, phosphocholine and pCF3-diEPP are potent agonists at unconventional nAChRs expressed by monocytic and macrophage-like cells. pCF3-diEPP inhibits the LPS-induced release of pro-inflammatory cytokines, while phosphocholine is ineffective. However, both agonists signal via nAChR subunits α7, α9 and/or α10 to efficiently down-modulate the ATP-induced release of IL-1β. Compared to phosphocholine, pCF3-diEPP is expected to have better pharmacological properties. Thus, low concentrations of pCF3-diEPP may be a therapeutic option for the treatment of inflammatory diseases including trauma-induced sterile inflammation.